1, 3-Dipolar cycloaddition of nitrones to oxa(aza)bicyclic alkenes. Issue 19 (22nd August 2019) - Yao, Yongqi; Yang, Wen; Lin, Qifu; Yang, Weitao; Li, Huanyong; Wang, Lin; Gu, Fenglong; Yang, Dingqiao
Abstract : A new 1, 3-dipolar cycloaddition of oxa(aza)bicyclic alkenes with nitrones has been developed without any catalyst and additive under mild conditions. The proposed concerted mechanism is investigated by DFT calculations of the reaction pathways. Abstract : A new 1, 3-dipolar cycloaddition of oxa(aza)bicyclic alkenes with nitrones has been developed. The operationally simple cycloaddition allows efficient synthesis of fused bicyclic tetrahydroisoxazoles bearing exo - and anti -five member heterocyclic rings (76–99% yields) without any catalyst and additive under mild conditions. The proposed concerted mechanism and the observed selectivity are investigated by DFT calculations of the reaction pathways. This mild and practical [3 + 2] cycloaddition provides an efficient route to access highly functionalized compounds.